China’s ADIZ over East China Sea : implications for ASEAN - Loh, Dylan Ming Hui (2014)
China’s decision to set up an ADIZ over the East China Sea has attracted strong criticism from major powers in the region but ASEAN’s response has been relatively muted. What implications does the ADIZ have for ASEAN?